Genetic and Epigenetic Signatures in Acute Promyelocytic Leukemia Treatment and Molecular Remission - Borutinskaitė, Veronika; Žučenka, Andrius; Vitkevičienė, Aida; Stoškus, Mindaugas; Kaupinis, Algirdas; Valius, Mindaugas; Gineikienė, Eglė; Navakauskienė, Rūta (Frontiers in Genetics, 2022)
Acute myeloid leukemia (AML) is an aggressive heterogeneous group of malignancies with different clinical behavior and different responses to therapy. For many types of cancer, finding cancer early makes it easier to treat. Identifying prognostic molecular markers and understanding their biology are the first steps toward developing novel diagnostic tools or/and therapies for patients with AML. In this study, we defined proteins and genes that can be used in the prognosis of different acute leukemia cases and find possible use in diagnostic and therapy. We analyzed newly diagnosed acute leukemia cases positive for t (15;17) (q22; q21) PML-RAR alpha, acute promyelocytic leukemia (APL). The samples of bone marrow cells were collected from patients at diagnosis stage, follow-up samples during standard treatment with all-trans retinoic acid, idarubicin, and mitoxantrone, and at the molecular remission. We determined changes in the expression of genes involved in leukemia cell growth, apoptosis, and differentiation. We observed that WT1, CALR, CAV1, and MYC genes’ expression in all APL patients with no relapse history was down-regulated after treatment and can be potential markers associated with the pathology, thereby revealing the potential value in this approach for a better characterization of the prediction of APL outcomes.